The Role of the Language Norm in the Definition Style Status: Peran Norma Bahasa alam Status Gaya Definisi - Rano Zaripova (Academia Open, 2019)
This paper investigates major points of the the role of the language norm in the definition of stylist status. On this case, research was conducted both methodologically and practically. Literature review of the different scholars who studied this topic was also covered by the author. The way of conclusion is linked with vivid suggestions of the research directing to further investigations as the whole.